1997
DOI: 10.1074/jbc.272.3.1484
|View full text |Cite
|
Sign up to set email alerts
|

Heparin and Heparan Sulfate Bind to Snake Cardiotoxin

Abstract: Cardiotoxins (CTXs) from cobra venom show cytotoxicity toward several cell types. They cause systolic heart arrest and severe tissue necrosis. Their interaction with phospholipids is established but by itself fails to explain the specificity of these toxins; other component(s) of membrane must, therefore, intervene to direct them toward their target. We herein show, for the first time, that sulfated glycosaminoglycans, heparin, heparan sulfate (HS), chondroitin sulfate (CS), and dermatan sulfate (DS), interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…GAGs have been shown to be a potential targets for cobra cardiotoxin with high affinity and specificity through a cationic belt at the concave surface of the polypeptide (14,15). We demonstrated that the binding site of VVA2 with GAGs was located at ␤-strands 7, 8, and ␣-helix D by affinity column chromatography, and preincubation of VVA2 with heparin prevented VVA2 oligomerization by liposomes.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…GAGs have been shown to be a potential targets for cobra cardiotoxin with high affinity and specificity through a cationic belt at the concave surface of the polypeptide (14,15). We demonstrated that the binding site of VVA2 with GAGs was located at ␤-strands 7, 8, and ␣-helix D by affinity column chromatography, and preincubation of VVA2 with heparin prevented VVA2 oligomerization by liposomes.…”
Section: Discussionmentioning
confidence: 80%
“…2C). Because cardiac myocytes contain a higher amount of GAGs on the cell membrane, it suggests that the HBS located at ␤-strands 7, 8, and ␣-helix D of VVA2 plays an important role in its cardiotoxicity (15).…”
Section: Fig 5 Vva2 Binds To Cell Membrane By Its Ctfmentioning
confidence: 99%
See 1 more Smart Citation
“…Hep-HMW accentuates the penetration of CTX into phospholipid membranes, as analyzed by Langmuir monolayer measurement under physiological salt condition (6). A similar heparin-enhanced binding of CTX A3 toward LPC micelles can also be monitored by Tyr intrinsic fluorescence intensity change of CTX A3 under 150 mM NaCl and 10 mM phosphate buffer at pH 7.4 ( Fig.…”
Section: Heparin-enhanced Ctx Binding To Lpc Micelles As Reflected Bymentioning
confidence: 85%
“…Heparin not only binds to homologous CTXs, with different specificity, but also promotes its penetration into phospholipid monolayer under physiological ionic conditions (6). Analysis of binding of 10 CTX homologues to heparin reveals a new heparin-binding structural motif by involving several positive residues at the concave surface of the three-finger toxin (7).…”
Section: From the Department Of Life Sciences National Tsing Hua Unimentioning
confidence: 99%